Profiling Kecerdasan Emosional Mahasiswa - Antonina Pantja Juni Wulandari (Bina Nusantara University, 2011)
Article pictures the emotional intelligent of college students. The emotional intelligent defines our potential to learn practical skills based on: self awareness, self controlling, motivation, empathy, social skill. From the five skills, it could be devided into two skills, i.e. individual and social competence. Individual competence is based on emotional intelligence about how we manage ourselves. Meanwhile, social competence is about how we handle our relationship with other people. From the research result, it can be concluded that emotional intelligence level of college students should be improved since there is none who has high score, especially about empathy as the lowest score.